Scattering of flat top soliton by external potential - Roslan, Iman Hanani; Mohd Busul Aklan, Nor Amirah (Kulliyyah of Science, IIUM, 2023)
This study examines the flat-top solitons scattering of Cubic Nonlinear Schrodinger Equation (NLSE) on external Delta potential. The interaction of flat-top solitons is analyzed using the variational approximation (VA) approach, by applying the Super-Gaussian ansatz as the trial function. From this method, the double equation of parameters are obtained; equation of width and center-of mass for the soliton. This equation described the interaction between the flat top soliton and external potential. After the scattering process, the flat-top solitons can be transmitted, reflected, or destroyed due to interacting with the potential when appropriate parameters are obtained.